Akuisisi Bahasa Anak Akibat Pengaruh Bahasa Minang dan Bahasa Melayu Malaysia - Hafizah; 'Ala, Faridatul (GERAM: Gerakan Aktif Menulis, 2022)
This study aimed to describe the language acquisition of children aged 5 to 6 years influenced by the Minang language and Malaysian language. The research method used was descriptive qualitative by describing children's language skills obtained through interviews with parents and observations. The data was obtained by listening, recording, transcribing, and analyzing. The research subjects were two children named Akbar, aged five years nine months, and Deryl, aged six years two months. The research results showed that the use of Minang language as an influence of his mother tongue and Malaysian language as the influence of the cartoons that he watched continuously in a child's language acquisition, while the use of Malaysian language as the influence of the Malaysian cartoons watched. The conclusion is that the Minang language and Malaysian language influence children's language acquisition.